2014
DOI: 10.1371/journal.pone.0100430
|View full text |Cite
|
Sign up to set email alerts
|

Isolate-Dependent Growth, Virulence, and Cell Wall Composition in the Human Pathogen Aspergillus fumigatus

Abstract: The ubiquitous fungal pathogen Aspergillus fumigatus is a mediator of allergic sensitization and invasive disease in susceptible individuals. The significant genetic and phenotypic variability between and among clinical and environmental isolates are important considerations in host-pathogen studies of A. fumigatus-mediated disease. We observed decreased radial growth, rate of germination, and ability to establish colony growth in a single environmental isolate of A. fumigatus, Af5517, when compared to other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 57 publications
2
33
0
Order By: Relevance
“…2B), which is consistent with previous reports of strain-dependent variations in growth rates of A. fumigatus isolates (21) as well as increased biomass production for some microbes during exposure to space environments (32). As early spore germination rates may favor niche exploitation and establishment of robust growth (21), we next sought to determine whether ISS isolates exhibited different germination dynamics in vitro . Figure 2C shows there were no differences in germination rates between ISSFT-021, IF1SW-F4, and CEA10 in liquid GMM, as nearly all spores germinated after an 8-h incubation, while Af293 showed a marked delay in germination.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…2B), which is consistent with previous reports of strain-dependent variations in growth rates of A. fumigatus isolates (21) as well as increased biomass production for some microbes during exposure to space environments (32). As early spore germination rates may favor niche exploitation and establishment of robust growth (21), we next sought to determine whether ISS isolates exhibited different germination dynamics in vitro . Figure 2C shows there were no differences in germination rates between ISSFT-021, IF1SW-F4, and CEA10 in liquid GMM, as nearly all spores germinated after an 8-h incubation, while Af293 showed a marked delay in germination.…”
Section: Resultssupporting
confidence: 92%
“…An examination of radial growth rates revealed that both ISS strains significantly outgrew both Af293 and CEA10 at all time points investigated (Fig. 2B), which is consistent with previous reports of strain-dependent variations in growth rates of A. fumigatus isolates (21) as well as increased biomass production for some microbes during exposure to space environments (32). As early spore germination rates may favor niche exploitation and establishment of robust growth (21), we next sought to determine whether ISS isolates exhibited different germination dynamics in vitro .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…6A). However, the virulence of Af5517 was decreased relative to that of Af293 (45), and BALB/c mice are less susceptible to IPA than other strains (29). It will be of interest to induce Th2 responses to more virulent isolates and include more susceptible mouse strains in future studies to observe the effect of these experimental manipulations on the role of eosinophils in Th2-mediated pathology.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that in the above mentioned studies in which discrepancies concerning IL-1 dependency arise, different A. fumigatus strains and morphotypes were used [29, 47, 49]. Interestingly, it is rapidly emerging that different strains of A. fumigatus can induce both dramatically different inflammatory responses [51, 52] and differing levels of virulence in vivo [52–54]. Interestingly, Rizzetto et al showed that the CEA10 isolate of A. fumigatus induced the greatest inflammation, which corresponded with its increased growth in immune competent mice [52].…”
Section: Role Of Il-1α and Il-1β During Invasive Fungal Infectionsmentioning
confidence: 99%